1995
DOI: 10.1063/1.359907
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stimulated currents in CdTe polycrystalline films

Abstract: Investigations of trapping centers have been carried out in CdTe polycrystalline films by using the thermally stimulated conductivity (TX) technique. The measurements were performed in the temperature range from 80 to 300 K. The TSC spectra showed three peaks related to three trapping levels with energy activations of 0.18, 0.29, and 0.32 eV, respectively. The two first trapping levels correspond to known acceptor centers in bulk CdTe previously reported. It is suggested that the level at 0.32 eV is due to gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The result of calculation gives m BE am 0 0X216f where m 0 is the free electron mass. If m BE is the same as the effective mass for holes, m h , then for f 3, m h am 0 0X65 which is in agreement with the adopted value of 0.64 [27]. This approach has also been used in estimating the number of bound electrons per molecule participating in dispersion in SnO 2 [26].…”
Section: Optical Dispersionsupporting
confidence: 71%
“…The result of calculation gives m BE am 0 0X216f where m 0 is the free electron mass. If m BE is the same as the effective mass for holes, m h , then for f 3, m h am 0 0X65 which is in agreement with the adopted value of 0.64 [27]. This approach has also been used in estimating the number of bound electrons per molecule participating in dispersion in SnO 2 [26].…”
Section: Optical Dispersionsupporting
confidence: 71%
“…A recent study using thermally stimulated conductivity has also indicated the presence of three trapping levels in CdTe with activation energies 0.18, 0.29 and 0.32 eV. The first two peaks were, however, found to correspond to two acceptor centres, while the third peak was attributed to grain boundary defects [44].…”
Section: Discussionmentioning
confidence: 97%